Characterization of anisotropic damage behaviour of recycled aluminium alloys AA6061 undergoing high velocity impact - Ho, C.S.; Ab Rani, M. A.; Mohd Nor, M. K.; Ma’at, N.; Hameed Sultan, M. T.; Lajis, M. A.; Yusuf, N. K. (Penerbit UTHM, 2019)
It is impossible to ignore the realm of the topics related recycling aluminium scraps. The recycled form of this material can be a good replacement for the primary resources due to the economic and environmental benefits. Numerous investigation must be conducted to establish the mechanical behaviour before the specific applications can be identified. In this research, Taylor Cylinder Impact tests used to investigate anisotropic damage behaviour in recycled aluminium alloy is presented. To be specific, by performing Taylor Cylinder Impact test at velocities ranging from 190m/s to 300m/s, anisotropic and damage characteristics can be observed in the samples as a function of the large stress, strain, and strain-rate gradient. The application of Taylor Cylinder Impact test as a technique to validate both the constitutive and dynamic fracture responses in such materials is also discussed. The structure of recycled aluminium AA6061 including the damage initiation and evolution are observed under optical microscope (OM) and scanning electron microscope (SEM). The results revealed that the damage evolution of the material change with the increasing impact velocity. Further, the digitised footprint analysis showed a pronounced anisotropic characteristic of the recycled aluminium AA6061.